Nanotherapy in Joints: Increasing Endogenous Hyaluronan Production by Delivering Hyaluronan Synthase 2. Issue 46 (24th September 2019) - Li, Huimin; Guo, Huilin; Lei, Chang; Liu, Li; Xu, Liqin; Feng, Yaping; Ke, Jin; Fang, Wei; Song, Hao; Xu, Chun; Yu, Chengzhong; Long, Xing
Abstract: Osteoarthritis (OA) is a common joint degenerative disease that causes pain, joint damage, and dysfunction. External hyaluronic acid (HA) supplement is a common method for the management of osteoarthritis which requires multi‐injections. It is demonstrated that biodegradable mesoporous silica nanoparticles successfully deliver an enzyme, hyaluronan synthase type 2 (HAS2), into synoviocytes from the temporomandibular joint (TMJ) and generate endogenous HA with high molecular weights. In a rat TMJ osteoarthritis inflammation model, this strategy promotes endogenous HA production and inhibits the synovial inflammation of OA for more than 3 weeks with one‐shot administration. Such nanotherapy also helps repairing the bone defects in a rat OA bone defect model. Abstract : Engineered nanoparticles are applied to deliver hyaluronan synthase 2 into synoviocytes of temporomandibular joint for the management of osteoarthritis. Endogenous hyaluronan production is therefore promoted and the synovial inflammation of osteoarthritis inhibited for more than 3 weeks with one‐shot administration.